B-Spline Functions for Solving nth Order Linear Delay Integro- Differential Equations of Convolution Type - Raghad Kadhim Salih; Atheer Jawad Kadhim; Fuad A. Al-Heety (Engineering and Technology Journal, 2010)
The paper is devoted to solve nth order linear delay integro-differentialequations of convolution type (DIDE's-CT) using Galerkin's method with B-splinefunctions. A new algorithm with the aid of Matlab language is derived to treatthree types (retarded, neutral and mixed) of nth order linear DIDE's-CT usingGalerkin's method with the aid of B-spline functions and Bool rule for calculatingthe required integrals for the proposed method where the procedure can be usedcomparatively greater computational efficiency. Comparison between approximateand exact results has been given in test examples for solving three types of linearDIDE's-CT of different orders for conciliated the accuracy of the approximateresults. Finally, the results are arranged in tabulated form and suitable graphing isgiven for every example.